DPOD2014: A new DORIS extension of ITRF2014 for precise orbit determination. Issue 1 (1st January 2019) - Moreaux, Guilhem; Willis, Pascal; Lemoine, Frank G.; Zelensky, Nikita P.; Couhert, Alexandre; Lakbir, Hanane Ait; Ferrage, Pascale
Abstract: To support precise orbit determination of the altimetry missions, the International DORIS Service (IDS) regularly estimates the DPOD (DORIS terrestrial reference frame for Precise Orbit Determination) solution which includes mean positions and velocities of all the DORIS stations. This solution is aligned to the current realization of the International Terrestrial Reference Frame (ITRF) and so, can be seen as a DORIS extension of the ITRF. In 2016, moving to the IDS Combination Center, the DPOD construction scheme changed. The new DPOD solution is produced from a DORIS cumulative position and velocity solution. We present the new methodology used to compute DPOD2014 and its validation procedure. In order to present geophysical applications and interpretations of these results, we show two examples: (1) the Gorkha earthquake (M7.8 – April 2015) generates a 3-D mis-positioning of nearly 55 mm of the EVEB DORIS station at the Everest base camp 90 km from the epicenter. (2) Applying the results the DPOD2014 realization, we show that the most recent vertical velocity of Thule, Greenland is similar to that observed between 2006 and 2010, indicating further ongoing ice mass loss in the Thule region of northwest Greenland.